2014
DOI: 10.1007/s12178-014-9244-9
|View full text |Cite
|
Sign up to set email alerts
|

Diaphyseal osteotomy after post-traumatic malalignment

Abstract: Tibia and femur shaft fractures can sometimes lead to post-traumatic deformities. Correction by means of circular external frames is a valuable option. The aim of this article is to give an overview of the problem and to focus on some important technical issues of the preoperative planning, the surgical procedures, and the postsurgical management of circular external fixators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…; Santoro et al. ). Second, the contralateral unaffected side is often used as a reference in arthroplasty surgeries to determine the size of an implant and its position, when the limb of interest is deformed by a fracture or a degenerative disease [e.g.…”
Section: Introductionmentioning
confidence: 98%
“…; Santoro et al. ). Second, the contralateral unaffected side is often used as a reference in arthroplasty surgeries to determine the size of an implant and its position, when the limb of interest is deformed by a fracture or a degenerative disease [e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Clamshell osteotomy reported by Russell et al [ 1 ] was preliminary experience at three institutions in USA. Two more case report of clamshell osteotomy have been reported in the literature [ 4 , 5 ]. Wilson et al reported a case of total knee arthroplasty after correction of extra-articular femoral deformity caused by malunited femoral shaft fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Computed Tomography in Veterinary Medicine: Currently Published and Tomorrow's Vision http://dx.doi.org/10.5772/intechopen.68556 use during/ postsurgery to assess bone angle and healing, particularly in companion animals such as cats and dogs [46,47].…”
Section: Clinical and Research Investigations Into Bone Tissuementioning
confidence: 99%